"Konvensyen keusahawanan” - Dim, AJ (Universiti Teknologi MARA, Sarawak, 2006)
While everybody was having their holiday, 15 students taking ETR 300 represented our university at the 'Konvensyen Keusahawanan Siswa IPTA dan Karniawan Nasional' on 12-14 Dec 05. The objective was to give students more exposure to entrepreneurship in their studies. The lucky students were accompanied by Miss Noni Haryati and Miss Fadhleen. The convention was organized by the Ministry of Entrepreneurship and Cooperation Development (MECD) in collaboration with University Technology MARA (UiTM) and MAKMUM. Y.B Dato' Khaled Nordin, Minister of Entrepreneurship and Cooperation Development officiated the convention. The activities included practical retailing of Sarawak craft products such as pua kumbu, batik Sarawak and craft accessories and also entrepreneurship-based competitions and forums. In addition, the participants collaborated with students from UiTM Sabah and Terengganu to contribute strategies for making entrepreneurship activities more effective in campus, at the 'Sidang Pleno'. Ideas included making ETR 300 more practical in terms of learning, internships with corporate organizations, and establishing entrepreneurship clubs on campus.